Corporate ESG Performance and Carbon Regulation in Achieving Sustainable Low Carbon Development - Khalisah Oktavia; Harry Z. Soeratin; Munasiron Miftah (PT Keberlanjutan Strategis Indonesia, 2026)
This paper aims to look at how corporate ESG performance and carbon regulation in achieving sustainable low-carbon development. Sustainable development is development that meets the needs of the current generation without compromising the ability of future generations to meet their own needs. To support sustainable development, companies can improve their Environmental, Social, and Governance (ESG) performance at the corporate level. In this context, Environmental, Social, and Governance (ESG) has attracted great interest among policymakers, companies, and researchers, given that ESG investments are highly relevant to achieving emissions targets. However, little attention has been paid to country-specific carbon policies and how they relate to ESG performance and corporate carbon reduction. This paper looks at the relationship between ESG performance and carbon regulation in China and Indonesia. The research method used is a literature study relevant to the theme of corporate ESG performance and carbon regulation in achieving sustainable low-carbon development.